The application of new methods of deactivation of engineering technique on the basis of impulse installations of fire extinguishing - Bobovich, Олег Леонидович (Chrezvychaynye situatsii: obrazovanie i nauka, 2008)
In the article the results of experimental researches on deactivation of engineering technique with the installation of impulse fire extinguishing («Vityas» IIF-1), executed on the polluted territories of the Gomel region (village Ugly, Narovlya district) are given.